2010
DOI: 10.3109/02699052.2010.506863
|View full text |Cite
|
Sign up to set email alerts
|

Anterior pituitary dysfunction in moderate-to-severe chronic traumatic brain injury patients and the influence on functional outcome

Abstract: These findings strongly suggest that patients who suffer head trauma should be routinely tested for anterior pituitary hormone deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 14 publications
3
23
0
Order By: Relevance
“…Only one study evaluated neurological prognosis using the extended Clasgow Outcome Scale and found no association with anterior pituitary disorders (37). Two studies (88 patients) suggested impaired functional status on the Functional Independence Measure scale with anterior pituitary disorders at rehabilitation admission (38,39), whereas two studies (117 patients) suggested impaired improvement of Functional Independence Measure scores during rehabilitation (38,40). Two studies (120 patients) showed impaired quality of life using the SF-36 questionnaire (37,41).…”
Section: Clinical Outcomes Of Anterior Pituitary Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study evaluated neurological prognosis using the extended Clasgow Outcome Scale and found no association with anterior pituitary disorders (37). Two studies (88 patients) suggested impaired functional status on the Functional Independence Measure scale with anterior pituitary disorders at rehabilitation admission (38,39), whereas two studies (117 patients) suggested impaired improvement of Functional Independence Measure scores during rehabilitation (38,40). Two studies (120 patients) showed impaired quality of life using the SF-36 questionnaire (37,41).…”
Section: Clinical Outcomes Of Anterior Pituitary Disordersmentioning
confidence: 99%
“…Only two studies quantitatively reported the effect of secondary brain injuries (hypoxemia and hypotension) on anterior pituitary disorders and found no association (33,37). One study observed a nonsignificant association between anterior pituitary disorders and diffuse axonal injury (40). Two studies evaluated MRI during the recovery phase and suggested that patients with pituitary disorders were more likely to have MRI pituitary abnormalities such as empty sella (33,46).…”
Section: Predictors Of Anterior Pituitary Disordersmentioning
confidence: 99%
“…There is evidence to demonstrate that following a traumatic brain injury (TBI), patients are at significant risk of developing post-traumatic hypopituitarism (PTHP) (1,2,3,4,5,6,7,8,9,10,11,12,13,14). Following TBI, patients have significantly reduced quality of life (QoL) and cognitive indices (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…GH deficiency has been associated with more severe deficits in memory, attention, executive function, mood, and sleep, as well as being associated with fatigue, many of which are often reported as postconcussive symptoms. [3][4][5][6][7][8][9][10] GH also may play a critical role in recovery, as it is involved in both myelin formation [11][12][13] and neuronal plasticity. [14][15][16][17] A number of potential pathophysiological mechanisms have been suggested as to how the pituitary gland is damaged.…”
mentioning
confidence: 99%